A Qualitative Study on Talent Management Strategies in State-Owned Enterprises - Muzanenhamo, Arvid; Rankhumise, Edward Malatse (CV. Literasi Indonesia, 2023)
The purpose of the study is to identify the employee retention strategies currently used in state-owned enterprises and their effectiveness in retaining employees. State-owned enterprises (SOEs) are increasingly concerned about employee retention due to skills shortages and labor turnover, which affect productivity. This has prompted this study to examine the talent management strategies used by state-owned enterprises since salaries seem to be low and unable to attract a skilled workforce. The study used qualitative research, and semi-structured interviews were administered to obtain data from Human Resource practitioners and departmental supervisors in a South African state-owned enterprise. The study found that employee wellness, more leave days, employee development, and permanent contracts are the main retention strategies used to improve employee satisfaction in public sector organizations. This study highlights the relevance of talent management strategies in achieving competitive advantage in public sector organizations.